Voluntary approaches and the organisation of environmental R&D - Joanna Poyago-Theotoky (Fondazione Eni Enrico Mattei (FEEM), 2000)
We consider a setting where firms undertake emission-reducing R&D and the regulator, who sets the emission tax, is unable to commit credibly. Firms are subject to research spillovers in emission reduction. We examine two regimes with respect to the organization of R&D: independent R&D and an environmental R&D cartel (ERC). Environmental R&D is higher in the ERC compared to independent R&D for small damages and also for large damages when R&D is efficient. In contrast, when damages are large and R&D is inefficient the opposite is true. The same ranking applies to the comparison of social welfare.
Keywords: O32; L13; Q28; 330; Environmental R&D Cartels; Environmental Research Joint Venture; Cooperative R&D; Emission Tax; Industrielle Forschung; Umwelttechnik; Ökosteuer; Selbstverpflichtung; Forschungskooperation; Theorie